Integrasi Digital Financial Literacy dalam Model Penerimaan Teknologi (Tam/Utaut2) Terhadap Adopsi QRIS - Santi Dwi Mulyati; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the integration of Digital Financial Literacy (DFL) has been incorporated in technology acceptance models especially the Technology Acceptance Model (TAM) and UTAUT2 and its effects on the acceptance of the Quick Response Code Indonesian Standard (QRIS) in developing countries. The review was performed with the Systematic Literature Review (SLR) method using analyzing 25 peer-reviewed articles that were published in 2019-2025 in accordance to the principles of PRISMA to advance the transparency of the selection, assessment, and synthesis. The results indicate that DFL is a major determinant resulting in the enhancement of perceived usefulness (PU), perceived ease of use (PEOU), trust, and risk awareness, hence escalating intention and actual behavior of user to adopt QRIS. DFL also supports important UTAUT2 variables, such as social influence, facilitating conditions, and habit. Moreover, the use of QRIS also leads to the digitalization of accounting by means of automated recording of transactions, better audit trail and financial reporting that is more efficient. However, the existing literature would be biased towards the behavioral intention as opposed to actual application in digital accounting practices, especially among micro, small, and medium enterprises (MSMEs). Altogether, DFL can be defined as a highly crucial facilitator of the adoption of digital payments and a driver of the modern accounting shift in the digital world.